2020
DOI: 10.3988/jcn.2020.16.1.53
|View full text |Cite
|
Sign up to set email alerts
|

Real-Life Effectiveness and Tolerability of Perampanel in Pediatric Patients Aged 4 Years or Older with Epilepsy: A Korean National Multicenter Study

Abstract: Background and Purpose The US Food and Drug Administration approval for perampanel has only recently been expanded to patients as young as 4 years, and so there have been few real-life studies of the effects of perampanel in pediatric patients. The aim of this study was to determine the long-term efficacy, factors affecting treatment response, and tolerability of perampanel as an add-on therapy in pediatric patients aged 4 years or older with epilepsy. Methods This multicenter retrospective observational study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
1
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 20 publications
6
37
1
2
Order By: Relevance
“…We identified reports in 257 patients of predominantly paediatric ages who received perampanel (182 in published literature and 75 in conference abstracts). The largest observational study with perampanel in paediatric patients (Hwang et al) reported data for 118 patients in generalised seizures, but no breakdown by seizure type or syndrome [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…We identified reports in 257 patients of predominantly paediatric ages who received perampanel (182 in published literature and 75 in conference abstracts). The largest observational study with perampanel in paediatric patients (Hwang et al) reported data for 118 patients in generalised seizures, but no breakdown by seizure type or syndrome [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…A multicenter, retrospective, observational study determined the 12-month efficacy and tolerability of perampanel as an adjunctive treatment in children ≥4 years of age with epilepsy in Korea (N=220). 20 Response and seizure freedom rates were 43.6% and 17.7%, respectively, with no significant differences across age groups. Adverse events were reported in 40% of patients, but most were of mild severity.…”
Section: Early Adjunctive Therapymentioning
confidence: 88%
“…Multiple randomized, double-blind, placebo-controlled trials and real-life studies have confirmed the efficacy and safety of perampanel as adjunctive therapy for focal and generalized seizures ( 7 – 10 ). Furthermore, perampanel was also efficacious and tolerated in children and adolescents ( 11 13 ). In addition, the good efficacy and safety of perampanel as a monotherapy has been demonstrated ( 14 ).…”
Section: Introductionmentioning
confidence: 95%